Aspect-Based Patterns for Grid Programming - Navarro, Luis Daniel Benavides; Douence, Rémi; Hermenier, Fabien; Menaud, Jean-Marc; Südholt, Mario (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2008: Anais do XX International Symposium on Computer Architecture and High Performance Computing, 2008)
The development of grid algorithms is frequently hampered by limited means to describe topologies and lack of support for the invasive composition of legacy components in order to pass data between them. In this paper we present a solution to overcome these limitations using the notion of invasive patterns for the construction of distributed algorithms, a recent extension of well-known computation and communication patterns. Concretely, we present two contributions. First, based on a study of how patterns are instantiated in NAS Grid, a well-known benchmark used for evaluating performance of computational grids, we show how invasive patterns can be used for the declarative definition of large-scale grid topologies and checkpointing algorithms. Second, we qualitatively and quantitatively evaluate how our approach can be used to implement the checkpointing on top of grid applications.